2006
DOI: 10.1007/s10980-005-5222-3
|View full text |Cite
|
Sign up to set email alerts
|

Extinction risk of wood-living model species in forest landscapes as related to forest history and conservation strategy

Abstract: Abstract. Dead wood is a critical resource for biodiversity in boreal forests. We analysed the persistence of five model species inhabiting dead wood. By parameterising a metapopulation model (the incidence function model), the model species were all assigned characteristics that makes it likely that they have disappeared from some (20%) forest landscapes with a long history of forest management. In the metapopulation model, a forest stand (5 ha) was regarded as a habitat patch. The amount of habitat in each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The colonisation ability affects which strategy that is the most efficient for preservation of this fauna. If the colonisation ability is low it is important that the conservation efforts are conducted close to sites where the target species are present (Huxel and Hastings 1999), while to protect species that colonise over long distances there should be more focus on sites where restoration efforts are inexpensive and may generate a quick increase in habitat quality (Ranius and Kindvall 2006). A low capacity to establish new populations far from present ones should especially be expected for species in habitats with low temporal and high spatial variability in carrying capacity, because they are assumed to have low dispersal rates (Southwood 1962;Johnson and Gaines 1990;Nilsson and Baranowski 1997;Travis and Dytham 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The colonisation ability affects which strategy that is the most efficient for preservation of this fauna. If the colonisation ability is low it is important that the conservation efforts are conducted close to sites where the target species are present (Huxel and Hastings 1999), while to protect species that colonise over long distances there should be more focus on sites where restoration efforts are inexpensive and may generate a quick increase in habitat quality (Ranius and Kindvall 2006). A low capacity to establish new populations far from present ones should especially be expected for species in habitats with low temporal and high spatial variability in carrying capacity, because they are assumed to have low dispersal rates (Southwood 1962;Johnson and Gaines 1990;Nilsson and Baranowski 1997;Travis and Dytham 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For conservation of species with a high capacity for colonisation of habitat patches far away other criteria should be used for cost-efficient conservation efforts. For instance, localities where it is possible to improve the habitat quality most quickly could be selected (Ranius and Kindvall 2006). …”
mentioning
confidence: 99%
“…Concerning the area effect, Lindenmayer et al (2015) performed the first experimental evaluation of the SLOSS (single large or several small areas for conservation) debate to VRH systems, and their results showed no significant area effect on bird species richness: thus IdS area could be adapted to local socio-economic requirements without compromising their value. Moreover, considering the extinction risk of saproxylic species, Ranius & Kindvall (2006) suggested that small reserves in landscapes characterized by commercial forestry have the advantage of containing higher quality fragments, which do not suffer the time-lag in deadwood restoration, as much as larger and younger areas.…”
Section: Landscape Approachmentioning
confidence: 99%